A Call to Otherness: Inscribing Digital Vernaculars into the Art Institution. (1st April 2021) - Menotti, Gabriel
In the mid-2010s, a number of renowned museums and galleries across the world held retrospective exhibitions positioning digital arts within western art history. While inscribing some techno-aesthetic forms and behaviours into the contemporary arts institution, these exhibitions nevertheless cemented the exclusion of others. By examining the role and shortcomings of curatorial practices in this process, this article seeks to frame curating as an art of inclusion able to carve institutional and epistemic space for otherness. In doing so, I argue for the relevance of devices for noticing, defined as a range of tactics that enable the apprehension of digital vernaculars ‐ everyday, 'lower' expressions of digital media culture ‐ within institutional sites and discourses. Through these tactics, curators may provoke under-represented cultural actors, forms and behaviours into recognition, reverse the violence of institutional occlusion, and fertilize art histories.